1997
DOI: 10.1074/jbc.272.50.31533
|View full text |Cite
|
Sign up to set email alerts
|

A New Mechanism-based Radical Intermediate in a Mutant R1 Protein Affecting the Catalytically Essential Glu441 inEscherichia coli Ribonucleotide Reductase

Abstract: The invariant active site residue Glu 441 in protein R1 of ribonucleotide reductase from Escherichia coli has been engineered to alanine, aspartic acid, and glutamic acid. Each mutant protein was structurally and enzymatically characterized. Glu 441 contributes to substrate binding, and a carboxylate side chain at position 441 is essential for catalysis. The most intriguing results are the suicidal mechanism-based reaction intermediates observed when R1 E441Q is incubated with protein R2 and natural substrates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
95
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(106 citation statements)
references
References 60 publications
11
95
0
Order By: Relevance
“…Interestingly, Cys-290 of T4 NrdD and Cys-439 of R1 could also be aligned to Cys-419 of PFL, one of the cysteines shown to form a transient thiyl radical in the PFL system (14 -16). Recent results for the class I RNR indicate involvement of a conserved carboxylate side chain in the steps following the abstraction of the 3Ј-hydrogen of the substrate (37)(38)(39). No direct counterpart of this residue is found in the class III RNR, instead formate may take this role.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Cys-290 of T4 NrdD and Cys-439 of R1 could also be aligned to Cys-419 of PFL, one of the cysteines shown to form a transient thiyl radical in the PFL system (14 -16). Recent results for the class I RNR indicate involvement of a conserved carboxylate side chain in the steps following the abstraction of the 3Ј-hydrogen of the substrate (37)(38)(39). No direct counterpart of this residue is found in the class III RNR, instead formate may take this role.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a-eliminations of ketyl radical anions are rapid and efficient processes widely applied in synthesis (Schmittel and Ghorai, 2001). However, while solution studies clearly favor the radical anion mechanism due to its lower barrier than the radical cation variant (Lenz and Giese, 1997), results from mutants of E. coli argue strongly against a stepwise radical anion mechanism (Persson et al, 1997). In an E441Q R1 mutant study, Stubbe and colleagues shut down the deprotonation pathway for the 39-ribonucleotide radical by exchanging E441 (glutamate) with Q441 (glutamine), but formation of the disulfide radical anion was observed nevertheless (Lawrence et al, 1999).…”
Section: Bereitgestellt Von | Universitaetsbibliothek Der Lmu Muenchenmentioning
confidence: 99%
“…The concept was first introduced by Zipse (1995), who suggested that a protonated glutamate could act as a bifunctional catalyst. A variation of this theme using only neutral molecules to avoid charge separation was computationally investigated slightly later (Siegbahn, 1998), but the experimental pH dependence of the enzyme activity (Persson et al, 1997), showing highest activity at pH 8, is more suggestive of the involvement of E441 in its deprotonated form wpK a(Glu-COOH) s4.4x. At about the same time, Zipse's hypothesis was refined by Stubbe and van der Donk (1998), who postulated that the E441 carboxylate group abstracts the proton at 39-OH simultaneously with the protonation of 29-OH by C225, leading to facile dehydration.…”
Section: Bereitgestellt Von | Universitaetsbibliothek Der Lmu Muenchenmentioning
confidence: 99%
See 1 more Smart Citation
“…With glu441 accepting a proton from the hydrogen of the hydroxyl group on C3' and cys225 donating a proton to the oxygen atom on C2', the radical on C3' is then transferred to C2' eliminating the hydroxyl group on C2' while releasing H 2 O and oxidizing the hydroxyl group on C3' to form 3'-keto-2-deoxyribonucleotides 3. 3,7,[21][22][23] The next step of the mechanism involves the radical on C2' abstracting the hydrogen atom on cys462, and cys225 donating the hydride ion to cys462 forming a disulfide radical anion 4. The radical from the cys225-cys462 is then transferred to C3' reducing the keto to hydroxyl with the help of glu441.…”
Section: H]-udp and [ 14 C]-mentioning
confidence: 99%